PENGEMBANGAN MODEL PENDIDIKAN LIFE SKILLS BERBASIS KEWIRAUSAHAAN MELALUI EXPERIENTIAL LEARNING - Iis Prasetyo; Entoh Tohani; Sumarno Sumarno (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
The existing life skill education program is not effective to reduce community poverty as the program just focus on producing more community hardskills than community softskills. This research aimed to create a model of entrepreneurship based 4-H lifeskills to decrease rural poverty. This research was conducted as from May through November 2013, in three regions of Gunung Kidul, Special Region of Yogyakarta. The data were collected by interview, documentation, observation and questionaire then analysed qualitatively and quantitatively. Research result shows: (1) most of the target research group members have dificulties in implementing several skills they obtained in the previous training; (2) the 4-H lifeskills model designed on the basis of empirical community condition is able to optimalize the use of the target group member resources; and (3) the model testing shows all of the three target groups have increasing mean of 4-H lifeskills perception. It means the model 4-H developed by researcher are effective.